Endoscopic Dacryocystorhinostomy With And Without Silicone Intubation: A Retrospective Study On Surgical Outcomes - Bashir, Sheraz; Mohsin Raza; Kundi, Nasir; Tahir, Muhammad; Khan, Muhammad Zubair; Khosa, Sherbaz Hussain (Journal of Rawalpindi Medical College, 2025)
Objective: To evaluate the effects of silicon stent intubation versus no intubation in endoscopic dacryocystorhinostomy (EnDCR). Methods: A Comparative Study Design was conducted in the ENT Department, Tertiary care hospital, Abbottabad, January 2022–August 2023. The study included 56 patients (28 in each group). Endoscopic DCR was done in one group with silicone stent intubation and other group without silicone intubation. Pre-operative and post-operative variables were evaluated for surgical outcomes using Munk scoring criteria. The absence of epiphora, a clear orifice, and the end of dacryocystitis episodes were considered signs of functional success. ANOVA tests were applied for comparisons. Results: Among the total 56 patients, 25(44.6%) were females and 31(55.4%) were male patients with a mean age of 36.8±11.9 years. Success rate after 18 months (Munk 0) is 67.9% in the non-stent group and 57.1% in the stent group. The success rate of both groups is nearly the same, which shows that the silicon intubation is not associated with the success rate of EnDCR. Conclusion: Given the comparable outcomes, non-intubated EnDCR should be considered the initial surgical option due to cost-effectiveness, reduced discomfort, and ease of postoperative care. However, this recommendation may not apply universally. Non-intubation is a reasonable first-line option but should be tailored to patient anatomy and risk factors. This study’s small sample size is a limitation, and larger randomised trials are needed. Keywords: Dacryocystorhinostomy, Epiphora, Endoscopy, Lacrimal Duct Obstruction